Phonetics of the Uzbek Language in Teaching Russian as A Foreign Language (Eurasian Journal of Learning and Academic Teaching, 2023)
The most important task of modern education in the framework of the development of a comprehensively developed personality and the study of the Russian language in a multiethnic university is the formation of phonetic skills, without which it is impossible to develop the communicative competence of students. Today, it is necessary to form and improve the methodology of teaching the Russian language so that it takes into account the characteristics of not only native speakers, but also those for whom Russian is a nonnative language. At the same time, the developed methodology must meet the requirements, regardless of their level of Russian language proficiency. The purpose of this article is to identify pedagogical conditions, as well as to develop and test a system of phonetic exercises for the formation of phonetic skills, the development of linguistic and communicative competence among students